Identification and Analysis of Accident Causes Using Human Factors Analysis and Classification System Approach in PT X - Narendradewo, Pandu; Gustomo, Aurik (Journal of Business and Management, 2013)
The researchÃ¢â‚¬â„¢s purpose is to reveal most intense human factor to cause accidents within PT X January to July 2012 period by using Human Factors Analysis and Classification System. Result was createdÃ‚Â by accumulating the accident hierarchy frequency from the Body Injured Incident Data record of six months along with the Injured Body Parts Map data to find out which part could be harmed on what level. Then from the summarized contents , human factors of accident would be extracted using Human Factors Analysis and Classification System (HFACS) approach, dividing each accident into specific category. To see which factor caused what, the accident hierarchy and the factors will be correlated to form a new variable,Ã‚Â reveals what kind of causes that appears the most and brought what type accident in result. That step will then completed by adding injured parts to the the one got found. The result overview pointed at revelation of Skill-Based Error and Physical Environment as the dominant of factors that lead to Medical Treatment accidents during the period. The result then would be a consideration to develop accident prevention program with focus on those two.Ã‚Â Keywords; Safety,Human Factors Analysis and Classification System, Accident.Category:Human Resources Management, Safety and Health Management